Vehicular suspension and propulsion using double sided linear induction machines - Cox, Tom; Eastham, Fred (2016)
This paper presents a new method of combined electromagnetic levitation and propulsion using a double sided pair of linear induction machines and a simple conductive sheet secondary. If the supply phase angle of one primary is modified with respect to that of the other, a controllable lift force can be developed on the conductive secondary and its load at any velocity or when stationary. Further, a resolution force is developed tending to drive the secondary into the center of the air gap, meaning that the system is inherently self-stabilizing without complex position feedback or control. This effect is studied and predicted using finite element analysis and then measured and confirmed using an experimental rig.